DEIXIS FOUND IN THE FIRST VICTORY SPEECH OF JOE BIDEN AS UNITED STATES PRESIDENT - Hery Ricca; Mhd Johan (Asosiasi Ide Bahasa Kepri, 2021)
This research aimed to analyze Deixis found in The First Victory Speech of Joe Biden as United States President On 7 November 2020. Deixis is a part of Pragmatics that being used to understand the words and phrases context which identify person, time, and place. The object of the research was to identify the deixis found in the Joe Biden’s speech by categorizing to person deixis, spatial deixis, and temporal deixis, and to find the most dominant deixis used in the speech. A qualitative research method was applied in this research. The data source in this research was the transcript of Joe Biden’s victory speech as the President of the United States. The data was collected by document review, and the data was analyzed by using theory of Miles and Huberman in Sugiyono (2012) which had three steps: Data reduction, data display, and conclusion drawing. The result showed as the most dominant deixis found in Joe Biden’s speech was person deixis with total 198 deixis and the least category found was temporal deixis with total 12 deixis